The Effect of Store Atmosphere on Repurchase Intention with Customer Satisfaction as Mediation Variable - Mohammad Miftah Ali; Eko Handayanto; Yulist Rima Fiandari (Universitas Muhammadiyah Malang, 2022)
This study aims to analyze the effect of the Store Atmosphere variable on the Repurchase Intention variable through Satisfaction as a mediating variable. A non-probability sampling of purposive sampling was used for the sampling technique, with the answer from 190 customers of Sinar Anugrah Store as the sample for this research. Furthermore, this research uses structural Equation Modeling – Partial Least Square (SEM-PLS) with the SmartPLS 3 program as a data analysis tool. The results show that the store atmosphere has a significant effect on repurchase intention, and the store atmosphere has a significant effect on customer satisfaction. Customer Satisfaction has no significant effect on Repurchase Intention. In addition, the results showed that customer satisfaction was not able to significantly mediate the store atmosphere on repurchase intentions.